A Prospective Evaluation of Serum Vitamin D (1, 25(OH)2 D3) and Endogenous Sex Hormone Levels in Colorectal Cancer Patients - Razak, Suhail; Alam, Iftikhar; Afsar, Tayyaba; Abulmeaty, Mahmoud M. A.; Almajwal, Ali; Jahan, Sarwat (Frontiers in Oncology, 2019)
Background Data on 25-OH VD concentrations and the associated factors in colorectal cancer (CRC) patients are scarce and need to be investigated. Methods A total of 200 CRC patients participated in this cross-sectional study conducted in Pakistan. Socio-demographic and other health data were collected in a pretested questionnaire. Serum measurements of Vitamin D (1, 25(OH)2 D3) levels and hormones were performed. Association of age, sex, primary site, effects of hormone therapy and stage of disease and selected reproductive health indicators on vitamin D status were primarily scrutinized by univariate analysis Results Mean age of the population was 55.3 years (±15.6; Range: 20-90 years). Estradiol concentration was considerably elevated in young females compared to young male patients (p<0.001). The concentrations of FSH, LH testosterone and estradiol were significantly lower in post-menopausal female CRC patients as compared to their male counterparts of old age (p, for all trends <0.05). Both LH and FSH showed significant gender difference but only in older patients. Level of estrogen was markedly decreased in older post-menopausal CRC patients compared to premenopausal CRC patients, which might be associated with CRC progression. In the group of women, who ‘ever used hormone therapy’ had differences of statistical significance (p, for all trends <0.05) in their mean serum 25-OH VD concentrations, while in the group of women who ‘never used hormone therapy’ had non-significant differences in their mean serum 25-OH VD concentrations (p, for all trends>0.05). High 25-OH VD concentrations were observed in women who had their menarche at the age of 15 years or more. Nulliparous women had the highest mean 25-OH VD concentrations as compared to unparious or multiparous women. In addition, women having their menopause at 40-44 years of age had the highest 25-OH VD concentrations, although the difference was not significant (p=0.08). Women who ‘never used any oral contraceptive’ had higher 25-OH VD concentrations as compared to those ‘whoever used oral contraceptives’.